Tinjauan Yuridis Atas Kelemahan Prosedural Pada Undang-Undang Nomor 2 Tahun 2004 Sebagai Sumber Tantangan Efektivitas Pengadilan Hubungan Indutrial - Muhammad Raqel Elang Pangestu; Aryadika Syaban; Muhammad Rifky Al Akmal (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The Unitary State of the Republic of Indonesia is fundamentally based on the principle of the rule of law, guaranteeing the fundamental right of citizens to fair legal certainty. Within the context of industrial relations, this guarantee is realized through Law Number 2 of 2004 concerning the Settlement of Industrial Relations Disputes, which is founded upon the principles of Expediency, Accuracy, Justice, and Low Cost. However, more than two decades following its implementation, there is a significant gap between the normative ideals and the procedural reality, centered on weaknesses within the procedural law. This normative research, based on a literature review and a statutory approach, deeply examines the procedural shortcomings of the Law on the Settlement of Industrial Relations Disputes. The research findings indicate that the pre-adjudication system (Bipartite and Mediation) fails to function as an initial filter due to the absence of firm sanctions for bad faith and the purely recommendatory nature of the mediator's advice, which is easily disregarded as stipulated in Article 13 of this Law. This failure leads to a backlog of cases in the Industrial Relations Court and violates the principles of Expediency and Low Cost. The second crucial weakness lies in the execution mechanism, where the Industrial Relations Court lacks independent authority and must rely on the District Court procedure as regulated in Article 57, resulting in an execution process that is slow, complicated, and prone to resistance, thus causing decisions that have obtained permanent legal force to fail in providing fair legal certainty. It is recommended that Article 13 be revised to grant the recommendation semi-executorial power if it is not rejected within seven working days, and it is also suggested that Arbitration be expanded to cover Rights.